Through A Classical Eye : Transcultural & Transhistorical Visions in Medieval English, Italian, and Latin Literature in Honour of Winthrop Wetherbee - Galloway, Andrew; Yeager, Robert F.; Wetherbee, Winthrop, 1938- (Book collections on Project MUSE., 2009)
Contains first-rate essays that demonstrate a range of strategies for undertaking transcultural and transhistorical studies of the late medieval period, and examines medieval literature and culture where English, Italian, and Latin materials overlap.